The growing movement for universal health coverage - Latko, Brian; Temporão, José Gomes; Frenk, Julio; Evans, Timothy G.; Chen, Lincoln C.; Pablos-Mendez, Ariel; Lagomarsino, Gina; Ferranti, David De (© 2011 The Lancet, 2017)
This note was published in The Lancet [© 2011 The Lancet] and the definite version is available at: http://www.thelancet.com/journals/lancet/article/PIIS0140-6736(10)62006-5/abstract